Teacher skill and stress levels: are they prepared for Response to Intervention? - Lavant, Sage; Ellenberger, Kelly (My University, 2009)
Elementary-level general education teachers' role-related stress and preparedness regarding Response to Intervention (RtI) were examined across 30 Western Wisconsin public school districts and seven counties. The relationship between role-related stress and preparedness, as well as how levels of both variables varied between counties, were examined. One-hundred and thirty-five general education teachers completed the Preparedness & Stress Measure (P & S Measure) online. Higher scores on the preparedness portion of the measure equated with higher levels of preparedness, while higher scores on the role-related stress portion equated with lower levels of stress. Statistical analyses revealed a significant positive correlation between the variables within counties, but did not reveal significant differences in levels of each variable between counties. Results from this study are lacking support from other literature, as this study's purpose was unique in providing empirical data concerning RtI preparedness and role-related stress. The importance of discussing findings with districts sampled is noted. As such discussion may contribute to improved professional development.
School Psychology Program Directed Research Project. 2009. Educational Specialist (Ed.S.) Degree. University of Wisconsin-River Falls. 32 p. Includes bibliographical references (p. 26-27).
Keywords: Teachers--Training of; Teachers--Self-rating of; RtI; Response to intervention; Teachers--Job stress